Factors Influencing Utilization of Health Services in Kenya: The Case of Homa Bay County - Stephen Odiwuor Otieno; David Macharia (Intelektual Pustaka Media Utama, 2014)
In order to improve efficiency in health service delivery in Kenya, the Ministry of Health has developed structures through inter-sectoral collaboration at various levels. Despite efforts by the government and key stakeholders to improve health sector, utilization of health services still remains a major challenge. The purpose of the study was to investigate factors that influence utilization of health services in Homa Bay County, Kenya. The study employed survey design and focused on health beneficiaries, District Health Management Team and other key health stakeholders, and used both quantitative and qualitative data. Quantitative data was collected through household interviews of 384 respondents and qualitative data was generated through Key Informant Interviews of 16 respondents. The study reveals that health financing, service delivery, quality, accessibility and equity influence utilization of health services in Homa Bay County. It is for these reasons that the study recommends that the government should allocate adequate budget towards health services, avail adequate trained health workers, and improve infrastructure in health facilities as well as drugs and other supplies. There is also need for further research on cultural factors influencing utilization of health services.